New species of Eugryllacris (Orthoptera: Gryllacrididae) from Yunnan, China - Liu, Jing; Yang, Hongqiang; Lu, Xiangyi; Bian, Xun (Zootaxa, 2021)
This paper describes one new species from Yunnan, China and reports the complete mitogenome. The new species differs from other species of the genus in markings on the frons and pronotum with 1 pair of black spots. The complete mitochondrial genome (mitogenome) of this new species was sequenced and analyzed using High-Throughput Sequencing. The mitogenome was 15513bp in length, comprising of 37 genes and a control region, and its gene order and location are identical to the ancestral insect mitogenome. The protein-coding genes (PCGs) had typical ATN initiation codons, and were terminated by typical TAN stop codons except for COII and ND5. Almost all tRNAs could be folded into the  typical cloverleaf secondary structure except for tRNASer(AGN). All the type specimens are deposited in the Guangxi Normal University.